DESIGN OF CENTRALIZED BIOGAS POWER PLANT USING COWS MANURE (CASE STUDY IN BANTUL, INDONESIA) - , DINTANI Y N N, Rachmawan Budiarto, S.T, M.T ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Since found in 1821, electricity has become one of most important needs to do daily activities. As the increasing of population and economy activities, electricity demand will grow as well. Indonesia is a development country which still depend its electricity supply on oil and gas sources. Since these sources can be diminished in any time, government should more invest on build renewable energy power plant. The main objective of this research is designing the first centralized biogas power plant that is suitable to be built in Bantul, Indonesia. This research is designed approaching to Linko Biogas Plants, Denmark. Parameters which are used to design this plant are feedstock type, hydraulic retention time, and temperature operation of digester. This plant utilizes gas turbine to generate electricity. To get the optimum electricity production, it varies the operation pressure of gas turbine. Manure, as feedstock for this plant, is collected from 8 sub-districts in Bantul. The farthest radius from plant site is Imogiri, that is 15 km. Manure is transported using 16 vacuum tankers which maximum capacity is 12,000 litres. All of feedstock will be mixed with water inside buffer tank. Then, digestion of this feedstock-water mixture takes place inside two stages digester, both are continuous flow type which is operates in mesophilic temperature (35oC). Total biogas yields from both digesters are 18,270 m3 per day. The raw biogas is being purified before it enters power generation stage. In power generation stage, gas turbine uses air as working fluid. Pressure ratio of air compressor is 10.50, whereas, pressure ratio for biogas compressor is higher by 1.1. The net electricity production of this plant is 963.42 kW per day.